PENGARUH FINANCIAL TECHNOLOGY, KARAKTERISTIK PERUSAHAAN, KARAKTERISTIK PEMILIK DAN LOKASI USAHA TERHADAP KEPUTUSAN PENDANAAN UMKM DI PROVINSI BALI - Natalia, Ni Putu; Wiagustini, Ni Luh Putu (Buletin Studi Ekonomi; VOLUME.27.NO.2.TAHUN.2022, 2022)
Funding decisions is financial decisions relating to investment spending made by the financial manager associated with how to finance the investment decisions that will be made and determine the composition of funding sources. Financial technology, company characteristics, owner characteristics and business location are said to have an influence in making funding decisions. Study aims to determine how the influence of financial technology, company characteristics, owner characteristics and business location on funding decisions with 100 respondens. The sample determination technique use a purposive sampling method based on MSMEs who know about Fintech lending, namely online lending and borrowing services. The method of collecting data is through a questionnaire. The data analysis technique used is multiple linier regression. The results indicate that financial technology, company characteristics, owner characteristics and business location have a positive effect on funding decisions.